Predictors of the worry about cancer recurrence among women with breast cancer - Masoumeh Safdari-Molan; Esmat Mehrabi; Roghaiyeh Nourizadeh; Reza Eghdam-Zamiri (BMC, 2023)
Abstract Introduction Worry about cancer recurrence is identified as the most common psychological burdens experienced by cancer patients and survivors. The present study aimed to determine the predictors of worry about cancer recurrence among women with breast cancer. Materials and methods This cross-sectional study was conducted on 166 women with breast cancer undergoing chemotherapy and radiotherapy, who referred to private and public oncology centers in Tabriz, Iran using the convenience sampling. Data collection tools were demographic and disease characteristics questionnaire, cancer worry scale, social support questionnaire, brief illness perception questionnaire, international physical activity questionnaire-short form, and The EORTC-in-patsat32. The data were analyzed using SPSS 25 software. Pearson correlation coefficient, independent t-test, ANOVA, and multivariate linear regression were used. Results In the present study, the mean (standard deviation) of score of worry about cancer recurrence was 17.41 (7.88), ranging from 8-32. The results revealed that the type of surgery, illness perception, satisfaction with care, and place of treatment were the most important predictors of worry about cancer recurrence, which explained 44.3% of the variance. Conclusion The enhancement of satisfaction with care and training coping strategies among individuals with high perceived severity of the illness contribute to the reduction of worry about cancer recurrence and adaptation to breast cancer.